Multi-locus genome-wide association study of chickpea reference set identifies genetic determinants of Pratylenchus thornei resistance - Channale, Sonal; Thompson, John P.; Varshney, Rajeev K.; Thudi, Mahendar; Zwart, Rebecca S. (Frontiers in Plant Science, 2023)
Pratylenchus thornei is an economically important species of root-lesion nematode adversely affecting chickpea (Cicer arietinum) yields globally. The broad host range of P. thornei, which includes many cereal and pulse crops, means P. thornei can cause extensive economic loss to whole farming systems. Due to the polygenic resistance of chickpea to P. thornei, we deployed a genome-wide association approach to identify genomic regions and candidate genes associated with P. thornei resistance in a reference set of chickpea genotypes. Phenotypic evaluation of 285 chickpea accessions was performed for two years (2018 and 2020) and 14 chickpea genotypes were found to be resistant to P. thornei. For the genome-wide association study (GWAS), we deployed six multi-locus GWAS models of which, FASTmrMLM was found to be the best performing model. In all, 24 significant quantitative trait nucleotides (QTNs) were identified, of which 13 QTNs were associated with lower nematode population density and 11 QTNs with higher nematode population density. These QTNs were distributed across all of the chickpea chromosomes, except chromosome 8. We identified, receptor-linked kinases (RLKs) on chromosomes 1, 4 and 6, GDSL-like Lipase/Acylhydrolase on chromosome 3, Aspartic proteinase-like and Thaumatin-like protein on chromosome 4, AT-hook DNA-binding and HSPRO2 on chromosome 6 as candidate genes for P. thornei resistance in the chickpea reference set. New sources of P. thornei resistant genotypes were identified that can be harnessed into breeding programs and putative candidate P. thornei resistant genes were identified that can be explored further to develop molecular markers and accelerate the incorporation of improved P. thornei resistance into elite chickpea cultivars.